Modulation of Insulin Resistance and β-Cell Function by Momordica charantia - Muhammad Fadhol Romdhoni; Dewi Karita; Amir (Universitas Muhammadiyah Malang, 2026)
Type-2 diabetes mellitus (T2DM) is characterized by insulin resistance and progressive pancreatic β-cell dysfunction. Therapeutic strategies that simultaneously improve insulin sensitivity and preserve β-cell secretory capacity are essential for effective metabolic control. Momordica charantia has been traditionally used as an antidiabetic agent; however, evidence regarding its effects on insulin resistance and β-cell function based on HOMA indices remains limited. This study aimed to evaluate the effects of Momordica charantia on insulin resistance and pancreatic β-cell secretory capacity in a rat model of T2DM using HOMA-IR and HOMA-β parameters. An experimental laboratory study with a post-test only control group design was conducted using 36 male Wistar rats randomly assigned into six groups (n = 6 per group). T2DM was induced using the streptozotocin–nicotinamide (STZ–NA) protocol. Treatment groups received oral Momordica charantia fruit extract at doses of 75, 150, and 300 mg/kg body weight, while a comparator group received vildagliptin. Fasting blood glucose and insulin levels were measured, and HOMA-IR and HOMA-β indices were calculated. Data were analyzed using one-way ANOVA and Kruskal–Wallis tests. Treatment groups Momordica charantia administration significantly reduced HOMA-IR values and increased HOMA-β values compared with the untreated diabetic group (p < 0.05). These findings indicate improved insulin sensitivity and partial restoration of pancreatic β-cell secretory capacity in treated rats. Administration of Momordica charantia improves insulin resistance and enhances pancreatic β-cell function in a T2DM rat model, supporting its potential role as a herbal-based adjunctive agent in the modulation of metabolic disturbances in type-2 diabetes mellitus.